ANALISIS BIAYA TRANSPORTASI DALAM DISTRIBUSI PENGIRIMAN BARANG (STUDI KASUS PADA PT RKO & RADO JAYA) - Amran, Kiagus Muhammad; Maryana, Diana (Universitas Logistik dan Bisnis Internasional, 2025)
This study aims to identify the various cost components that constitute transportation costs in the goods distribution process at PT Riko & Rado Jaya. The research employs a descriptive analysis technique to evaluate data, perform calculations on numerical values, and determine the costs included in transportation expenses. The results indicate that the transportation costs at PT Riko & Rado Jaya consist of investment costs, fixed costs, and variable costs. The distribution costs vary depending on the delivery route, with the highest distribution cost found on the SU-TGR route, covering a distance of 1,863 km and amounting to IDR 1,406,565. Among all components, variable costs contribute the largest percentage to the total transportation cost.